Widespread innervation of motoneurons by spinal V3 neurons globally amplifies locomotor output in mice - Han Zhang; Dylan Deska-Gauthier; Colin S. MacKay; Krishnapriya Hari; Ana M. Lucas-Osma; Joanna Borowska-Fielding; Reese L. Letawsky; Vladimir Rancic; Turgay Akay; Keith K. Fenrich; David J. Bennett; Ying Zhang (Cell Reports)
Summary: While considerable progress has been made in understanding the neuronal circuits that underlie the patterning of locomotor behaviors, less is known about the circuits that amplify motoneuron output to adjust muscle force. Here, we demonstrate that propriospinal V3 neurons (Sim1+) account for ∼20% of excitatory input to motoneurons across hindlimb muscles. V3 neurons also form extensive connections among themselves and with other excitatory premotor neurons, such as V2a neurons. Optical activation of V3 neurons in a single segment rapidly amplifies locomotor-related motoneuron output at all lumbar segments in in vitro spinal cord and the awake adult mouse. Despite similar innervation from V3 neurons to flexor and extensor motoneuron pools, V3 neurons preferentially activate extensor muscles. Genetically or optogenetically silencing V3 neurons leads to slower and weaker mice with a reduced ability to adjust extensor muscle force. Thus, V3 neurons serve as global command neurons that amplify locomotion intensity.